2015
DOI: 10.1590/1980-5497201500040020
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid intake and metabolic syndrome among overweight and obese women

Abstract: ABSTRACT:Objective: To examine relations between fatty acids intake and metabolic syndrome (MetS) status among overweight and obese women (n = 223). Methods: This was a cross-sectional study. The physical and laboratory tests included anthropometry, body composition evaluation and measurements of blood pressure, fasting blood glucose, insulinemia and lipid profiles. A three-day food diary was used to evaluate fatty acids consumption. Statistical analysis included χ 2 test and odds ratio measurements. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
0
4
0
1
Order By: Relevance
“…Increasing evidence suggests that overproduction of fatty acids by the FAS system is correlated with MetS and various cancers 12,13,14,15,16,17,41 . Inhibition of FAS activity significantly induces tumor cell apoptosis, suppresses tumor cell metastasis and improves insulin sensitivity 33,42,43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that overproduction of fatty acids by the FAS system is correlated with MetS and various cancers 12,13,14,15,16,17,41 . Inhibition of FAS activity significantly induces tumor cell apoptosis, suppresses tumor cell metastasis and improves insulin sensitivity 33,42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of FAS activity significantly induces tumor cell apoptosis, suppresses tumor cell metastasis and improves insulin sensitivity 33,42,43 . Hence, hFASN is considered to be a promising anti-MetS and anti-tumor drug target for clinical therapy, and several specific inhibitors for interfering with the enzymatic activity of hFASN have been developed 3,41,42,43,44,45,46 . Unfortunately, most of these compounds have limited applications in clinical scenarios due to severe side effects or modest potency 23,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, changes in lifestyle have promoted a significant increase in the intake of lipids and an increase in body fat, which is largely a result from a positive energy balance, which is favored by a diet with high energy density such as the high-fat-diet (HFD) [1,2]. If this pattern of consumption is continuous it may contribute to the development of obesity, a disease considered a global epidemic, which is closely related to heart disease, diabetes, kidney disease, hepatic steatosis, metabolic syndrome, and certain types of cancer [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study, relations between fatty acids intake and metabolic syndrome (MetS) status among overweight and obese women were addressed. Overweight women with MetS consumed higher amounts of monounsaturated fatty acids, polyunsaturated fatty acids, and linoleic acid compared to overweight women without MetS [52]. Further, in a large sample of Swedish middle-aged men (total 2322), a follow-up of 32 years showed that raised amounts of palmitic, palmitoleic, and oleic acid were related to a higher risk for stroke/transient ischemic attack, whereas a higher proportion of linoleic acid was protective [53].…”
Section: Monounsaturated Fatty Acids (Mufas)mentioning
confidence: 93%